Alterations of Retinal Pigment Epithelium–Photoreceptor Complex in Patients with Type 2 Diabetes Mellitus without Diabetic Retinopathy: A Cross-Sectional Study - Zheren Xia; Hao Chen; Suilian Zheng (Journal of Diabetes Research)
Aim. A cross-sectional study was performed to examine the alterations of the retinal pigment epithelium– (RPE–) photoreceptor complex layer in type 2 diabetes mellitus (DM) without diabetic retinopathy (DR), using spectral-domain optical coherence tomography (SD-OCT). Methods. Patients with type 2 DM without DR and healthy controls without DM were recruited. All participants underwent examinations including SD-OCT. The thickness measurements of the retinal neural layers were calculated after automatic segmentation. An independent-sample t-test was used to compare the means of the thickness of retinal neural layers in patients with DM and healthy controls. Results. Sixty-seven eyes from 67 patients with DM and 30 eyes from 30 healthy controls were included in this study. No significant differences were found in age (P = 0.601), gender (P = 0.560), axial length (P = 0.414), best-corrected visual acuity (P = 0.963), or intraocular pressure (P = 0.112) between the two groups. There were significant increases in the hemoglobin A1c value (P < 0.001) and mean thicknesses of the RPE–photoreceptor complex layer in the foveal area (P = 0.027) and paracentral area (P = 0.001) in the DM group compared to the control group, whereas the thickness of the retinal nerve fiber and ganglion cell layers in the foveal and paracentral areas between the two groups showed no significant differences. Conclusion. Lesions in the RPE–photoreceptor complex are present without vascular abnormalities, which may precede the alterations of ganglion cells in patients with type 2 DM.